Pengaruh Computer Anxiety, Computer Attitude dan Computer Self-Efficacy Terhadap Literasi Digital Pelaku UMKM Industri Pangan - Lomagio, Afriana; Fitrianti, Fitrianti (Gorontalo Accounting Journal, 2022)
The study was conducted to determine how much computer anxiety, computer attitude, and computer self-access acy affect the digital literacy of the industrial food umkm of boalemo district. The study USES a quantitative method. The methods of data collection used in the study are carried out through field observation, disseminating questionnaires, interviews, documentation and literature studies. As for the population in this study are all the perpetrators of the food industry in the boalemo district with sample withdrawal using sampling cluster methods in tilamuta district. The data analysis technique used in the study is a linear, linear regression analysis technique with the help of version 24 SPSS software. The study suggests that (1) computer anxiety, computer attitude and computer self acy both simultaneously affect the digital literacy of umkm perpetrators, (2) computer anxiety can also have a partial negative and significant impact on the digital literacy of umkm perpetrators, And (4) computer self literacy has a partial positive and significant impact on the digital literacy of umkm perpetrators.